Implementation of the Transparency Principles and Accountability of Indonesian Zakat Management Organizations through Providing Information and Financial Reports on the Website - Ari Astuti; Bijan Bidabad (Socio-Economic and Humanistic Aspects for Township and Industry, 2024)
Zakat has an important role in driving social and economic welfare in Indonesia. However, to ensure its effectiveness, it is important to ensure transparency and accountability in the management of zakat by Zakat Management Organizations (OPZ). This study aims to explore the implementation of transparency and accountability principles of OPZ in Indonesia through the provision of information and financial reports on their websites. Using descriptive qualitative method, data was obtained from 12 LAZNAS that published their financial reports for 2019-2021. The results show that most OPZs have not maximally utilized the internet for financial information. However, OPZs that have published financial reports on their respective websites can be categorized as "good" in implementing accountability and transparency. Suggestions include increasing the utilization of the website by OPZ, the establishment of regulations by related institutions, and supervision by the government to improve OPZ accountability. Thus, it is expected that the level of public trust in OPZ can increase, supporting the acceptance of zakat, infaq and sadaqah.